Flow-induced vibration response analysis of windshield of high-speed train based on proper orthogonal decomposition and pseudo excitation method - Xiang Liu; Pengxiang Lv; Xiao Liu (Engineering Applications of Computational Fluid Mechanics)
The flow-induced vibration of the outer windshield of high-speed train intensifies as the train's speed increases, impacting stability and safety during operation. The vibration characteristics of outer windshields are crucial for optimizing higher-speed train design. In this paper, proper orthogonal decomposition (POD) in conjunction with the pseudo excitation method (PEM) is applied for flow-induced vibration analysis of windshield. The dynamic model of the windshield is established by mode superposition method to reduce the degrees of freedom of the windshield structure. By utilizing the proper orthogonal decomposition and pseudo excitation method (POD-PEM), the accurate frequency characteristics of the flow-induced vibration dynamics of the windshield can be obtained efficiently. The calculation results are compared with the time-domain response to verify the accuracy and the proposed method. The results from the reduced-order model indicate that this method significantly improves the calculation efficiency. This study can provide a reference for the evaluation and optimization of high-speed train windshields.